2021
DOI: 10.36418/syntax-literate.v6i10.4360
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Teaching Techniques Used In Teaching Reading Comprehension By English Teachers At Madrasah Aliyah Pasangkayu

Abstract: This research was aimed at finding out the teaching techniques used in teaching reading comprehension by English teachers from four Madrasah Aliyah at Pasangkayu Regency. MAN Pasangkayu, MA DDI Pasangkayu, MA DDI Kasoloang and MA DDI Darul Ulum. This research applied mix method approach. The respondents of this research were 8 English teachers. The instrument for collecting the data was a questionnaire and interview. Quantitative data were collected and analyzed in the first phase of the research and qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In addition, at the end it is shown that the poor hate the rich, which is shown by the stabbing scene. This is due to differences in mindset and point of view that cause mental blocks and differences in daily habits (Mukrim, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, at the end it is shown that the poor hate the rich, which is shown by the stabbing scene. This is due to differences in mindset and point of view that cause mental blocks and differences in daily habits (Mukrim, 2021).…”
Section: Discussionmentioning
confidence: 99%